Protecting Rural India from COVID-19: Second wave 2021 - Raman Kumar (Wolters Kluwer Medknow Publications, 2021)
The population of India is 1.380 billion. Sixty-five percent of the Indian population lives in rural habitat. However, the healthcare facilities are largely concentrated in urban areas. The first peak of the COVID pandemic peaked in September 2020 gradually declining till mid-February 2021. Rural India has often travel to urban centers for treatment and disease management. The second wave started in March and peaked with a daily number ranging more than 400,000 till May 10th. It is now spreading into rural India. The culture of access to healthcare among rural populations is different from the urban areas. Facilities and infrastructure are also scarce as compared to the urban areas.